Exploring governance for a One Health collaboration for leptospirosis prevention and control in Fiji: Stakeholder perceptions, evidence, and processes. (30th March 2018) - McPherson, Anna; Hill, Peter S.; Kama, Mike; Reid, Simon
SUMMARY: Fiji has a high burden of leptospirosis, with endemic infection and epidemic outbreaks with high mortality, often associated with flooding and cyclones. As a zoonosis, leptospirosis control requires interventions in sectors beyond the usual control of health—in Fiji, the dairy and sugar industries, and water and sanitation and rodent control in communities. This paper presents the findings of qualitative research to inform policy around governance for a One Health multisectoral approach to leptospirosis control. Methods: Key informants from relevant government agencies and industry organizations were interviewed in late 2014, and the interviews analyzed and triangulated with documentary analysis. Findings: The analysis identified 5 themes: perceptions of the impact of leptospirosis, governance processes, models for collaboration, leptospirosis control, and preferred leadership for leptospirosis management. Data were limited, with poor communication between ministries, and limited awareness of leptospirosis outside outbreaks. Collaboration during outbreaks was positive but not sustained in endemic periods. Mechanism for enhanced collaboration was developed for endemic and outbreak situations. Conclusion: The findings informed a One Health governance approach to leptospirosis, framed within a National Strategic Plan, with a specific National Action Plan for Leptospirosis. The process provides a research based One Health template for application to other zoonotic diseases.